北極振動と南極振動の「メタ・テレコネクション」～両半球をつなぐ航路は何か～ - 立花, 義裕; タチバナ, ヨシヒロ; Tachibana, Yoshihiro; 本田, 明治; ホンダ, アキハル; Honda, Akiharu; 中村, 哲; ナカムラ, テツ; Nakamura, Tetsu (三重大学, 2019)
application/pdf 北極振動は北半球で最も卓越する大気変動で，北半球の異常気象に影響する．一方，南半球には南極振動があり，オゾンホールとの強い関連から地球環境に極めて重要である．両極は地理学的に最も遠くに位置することから，両振動の共変の存在を調べた研究は無かった． 本研究はこの2つの振動が同期して変動する仮説「メタ・テレコネクション」を提唱し，大気再解析・大循環モデルを用いた解析を行った．その結果，2月と10月は両振動が有意に正相関でシンクロしていたことを示した．またシンクロの原因として，片方の極で発生する成層圏突然昇温に伴う成層圏子午面循環が，熱帯の対流活動に影響し，反対の極へ遠隔的に影響する可能性を指摘した． The Arctic Oscillation (AO) and the Antarctic Oscillation (AAO) are dominant atmospheric variability patterns in the Northern and Southern Hemispheres, respectively. Each is a pressure seesaw between the pole and the midlatitudes that remotely affects weather, climate, and environment around the world. We showed interhemispheric in-phase synchronization between the AO and AAO in October and February, and we also found decadal-scale variation of the synchronicity. Because the vertical structure of the AO-AAO synchronization extends from the troposphere to the stratosphere, stratospheric variations may be responsible for the synchronization. This finding of AO-AAO synchronization points the way to a better understanding of past, present, and future pole-to-pole climatic relationships and improvements in long-term weather forecasts. 2016年度～2018年度科学研究費補助金(挑戦的萌芽研究)研究成果報告書 16K13880 research report